Chorioallantoic membranes of embryonated chicken eggs as an alternative system for isolation of equine influenza virus - Ilona Marcelina Gora; Malgorzata Kwasnik; Jan Franciszek Zmudzinski; Wojciech Rozek (Virology Journal, 2017)
Abstract Background Influenza virus isolation in embryonated chicken eggs (ECEs) is not applicable for rapid diagnosis, however it allows the recovery and propagation of the viable virus. A low number of infectious virus particles in the swabs, poor quality of samples or individual strain properties can lead to difficulties during the virus isolation process. We propose to utilize chorioallantoic membranes (CAM) of ECEs with the assistance of real-time RT PCR to facilitate equine influenza virus isolation. Methods Real-time RT PCR was used to detect influenza virus genetic material in amniotic/allantoic fluids (AF) and CAM of ECEs. Haemagglutination assay was used for AF. We used highly diluted virus as a substitute of clinical specimen for ECEs inoculation. Results Our study demonstrated that real-time RT PCR testing of CAM homogenates was more useful than testing of AF for EIV detection in ECEs. Positive results from CAM allowed to select the embryos from those with haemagglutination assay (HA) - and real-time RT PCR-negative AF for further passages. Using homogenates of CAM for subsequent passages, we finally obtained HA-positive AF, which confirmed virus replication. Conclusion We postulate that real-time RT PCR testing of CAM homogenates and their subsequent passages may facilitate the isolation of equine influenza viruses.